2023
DOI: 10.3390/cancers15030733
|View full text |Cite
|
Sign up to set email alerts
|

Liver Resection and Transplantation Following Yttrium-90 Radioembolization for Primary Malignant Liver Tumors: A 15-Year Single-Center Experience

Abstract: Radioembolization (RE) may help local control and achieve tumor reduction while hypertrophies healthy liver and provides a test of time. For liver transplant (LT) candidates, it may attain downstaging for initially non-candidates and bridging during the waitlist. Methods: Patients diagnosed with HCC and ICC treated by RE with further liver resection (LR) or LT between 2005–2020 were included. All patients selected were discarded for the upfront surgical approach for not accomplishing oncological or surgical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The estimated survival rate in our whole patient cohort was 82.0% and 60.5% at 6 and 12 months after TARE, respectively, which is similar to other studies evaluating patients with unresectable HCC, also regarding the proportion of patients who underwent LT after bridging TARE [ 11 , 23 , 24 ]. Despite our hospital being a specialized liver transplantation center, only approx.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The estimated survival rate in our whole patient cohort was 82.0% and 60.5% at 6 and 12 months after TARE, respectively, which is similar to other studies evaluating patients with unresectable HCC, also regarding the proportion of patients who underwent LT after bridging TARE [ 11 , 23 , 24 ]. Despite our hospital being a specialized liver transplantation center, only approx.…”
Section: Discussionsupporting
confidence: 88%
“…In this context, a bridging therapy, such as transarterial radioembolization (TARE) before liver transplantation (LT), is applied. The effectiveness of locoregional, neoadjuvant therapies for this purpose has been demonstrated by several studies [ 5 , 6 , 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Studies directly comparing TARE with TACE found a higher disease control rate, significantly better overall and intrahepatic PFS, and better survival outcomes in the patients treated with TARE even with advanced disease [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, approximately 854,000 cases of liver cancer were diagnosed and 810,000 patients died [ 5 ]. The most common type of primary liver cancer is hepatocellular carcinoma (HCC), followed by intrahepatic cholangiocarcinoma (ICC), comprising approximately 80% and 15%, respectively [ 5 , 6 , 7 ]. For HCC without cirrhosis, surgical resection offers the best chance of cure, but most cases are unfortunately diagnosed at an advanced stage that reduces the chances of successful surgery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common type of primary liver cancer is hepatocellular carcinoma (HCC), followed by intrahepatic cholangiocarcinoma (ICC), comprising approximately 80% and 15%, respectively [ 5 , 6 , 7 ]. For HCC without cirrhosis, surgical resection offers the best chance of cure, but most cases are unfortunately diagnosed at an advanced stage that reduces the chances of successful surgery [ 7 ]. Furthermore, the recurrence rate remains high even if a patient with HCC undergoes curative resection, with 5-year recurrence rates of up to 70% [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%